Analisis Pergaulan Bebas Dalam Film "Dua Garis Biru" - Arfian Suryasuciramdhan; Nazlah Azzahra; Rini Sartika; Vina Lestari (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Film is a mass communication medium, which has an influence on society. Film is also a form of message consisting of various signs and symbols that form a system of meaning so that people can interpret it differently, depending on the reference and the person's thinking ability. The film Two Blue Lines by Gina S. Noer raises the theme of teenage pregnancy. The interpretation of conflict in scenes in this film is the background for this research to look at the reception of the audience's position